Multiple solutions of the unsteady hybrid nanofluid flow over a rotating disk with stability analysis - Pop, Ioan Mihai; Waini, Iskandar; Ishak, Anuar (Elsevier Ltd, 2022)
The present study attempts to analyze the unsteady flow over a rotating disk in a hybrid nanofluid with suction and deceleration effects. The partial derivatives of multivariable differential equations are converted to ordinary differential equations using appropriate transformations. The bvp4c function in MATLAB software is employed to solve the mathematical model. The outcomes show that multiple solutions are verifiable in certain operating parameters. The stability of the multiple solutions over time is investigated. It is discovered that the first and the second solutions are stable and physically relevant, whereas the third solution is unstable as time evolves. Moreover, the stronger deceleration contributes to enhancing the skin friction coefficient in the radial direction Rer1/2Cf and in the azimuthal direction Rer1/2Cg, for the first and third solutions whereas the second solution reduces. The values of Rer1/2Cf and Rer1/2Cg for the third solution enhance in the presence of suction, while the opposite behaviors​ are observed for the first and second solutions. The enhancement of the local Nusselt number Rer−1/2Nur on all solutions is noticed with the imposition of suction on the surface and stronger deceleration strength.